Perencanaan Pengadaan Sarana dan Prasarana Pendidikan di SDIT An-Nuriyah Sekayu-Musi Banyuasin - Riandini, Tias; Febriyanti, Febriyanti; Zulkipli, Zulkipli (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to understand how the planning for the procurement of educational facilities and infrastructure is carried out at SDIT An-Nuriyah Sekayu-Musi Banyuasin. The researcher uses a descriptive qualitative approach with a qualitative research type. The informants in this study include the Foundation Head, School Principal, Vice Principal for Facilities, and Administrative Staff. Data collection techniques used are interviews, observations, and documentation. The data analysis techniques include data reduction, data presentation, data verification, and conclusion drawing. The validity of the data in this research is tested using source triangulation and technique triangulation. The results of this study indicate that the planning for the procurement of educational facilities and infrastructure at SDIT An-Nuriyah Sekayu, Musi Banyuasin, has been carried out quite well. This can be seen from setting targets and objectives in the procurement of educational facilities and infrastructure, formulating the current state of procurement, identifying all the facilitators and obstacles in procurement, and developing a procurement plan for educational facilities and infrastructure